A novel phosphoglucomutase‐deficient mouse model reveals aberrant glycosylation and early embryonic lethality. Issue 5 (21st June 2019) - Balakrishnan, Bijina; Verheijen, Jan; Lupo, Arielle; Raymond, Kimiyo; Turgeon, Coleman; Yang, Yueqin; Carter, Kandis L.; Whitehead, Kevin J.; Kozicz, Tamas; Morava, Eva; Lai, Kent
Abstract: Patients with phosphoglucomutase (PGM1) deficiency, a congenital disorder of glycosylation (CDG) suffer from multiple disease phenotypes. Midline cleft defects are present at birth. Overtime, additional clinical phenotypes, which include severe hypoglycemia, hepatopathy, growth retardation, hormonal deficiencies, hemostatic anomalies, frequently lethal, early‐onset of dilated cardiomyopathy and myopathy emerge, reflecting the central roles of the enzyme in (glycogen) metabolism and glycosylation. To delineate the pathophysiology of the tissue‐specific disease phenotypes, we constructed a constitutive Pgm2 (mouse ortholog of human PGM1 )‐knockout (KO) mouse model using CRISPR‐Cas9 technology. After multiple crosses between heterozygous parents, we were unable to identify homozygous life births in 78 newborn pups ( P = 1.59897E‐06), suggesting an embryonic lethality phenotype in the homozygotes. Ultrasound studies of the course of pregnancy confirmed Pgm2‐deficient pups succumb before E9.5. Oral galactose supplementation (9 mg/mL drinking water) did not rescue the lethality. Biochemical studies of tissues and skin fibroblasts harvested from heterozygous animals confirmed reduced Pgm2 enzyme activity and abundance, but no change in glycogen content. However, glycomics analyses in serum revealed an abnormal glycosylation pattern in the Pgm2 +/− animals, similar to that seen in PGM1‐CDG.